TESISINDUKSI KETAHANAN TANAMAN JAGUNG (Zea mays L.) TERHADAP PENYAKIT BULAI MELALUI SEED TREATMENT SERTA PEWARISANNYA PADA GENERASI S1 - , HOERUSSALAM; , Dr. Ir. Aziz Purwantoro M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Resistance to disease is an important trait in breeding influencing quality and ultimately the crop yield. The induction of systemic resistance could be performed to improve plant resistance to disease which is stimulating the plant defense system by using elicitor application. It involves the coordination and expression of a particular gene called SAR genes and characterized by the accumulation of certain compounds such as or jasmonate acid. The experiment consists of four steps. First step is preliminary experiment to select the best non pathogenic rhizobacteria as biological elicitor. Selection of their bacteria based on hypersensitive assesment, effect of rhizobacteria application to seed viability and diseses inhibition. The main experiment consist of three experiments. First, Selection of promising line. This experiment is aimed to obtain the best line that possess highest raising resistance and most responsive to treatment. This research utilized six F1 hybrids of maize i.e. C02, C05, C13, C19, C20, and SC-139 4D. Four elicitors were tested as treatment namely non pathogenic rhizobacteria Bio1 dan Bio2, Salicylic acid (Abio1) and Benzothiadiazole-S-Methy/BTH (Abio2) by seed treatment. As control was used Fungicides Dimethomorph+Metalaxyl. Experiment was conducted at open field using spreader as inoculum source. Treated seeds then were planted and observed until 42 days after planting. Resistance evaluation was done by comparing origine resistance with induced resistance. Resistant plant was self-pollinated to obtain S The result revealed C20 is the most responsive to four kinds of elicitor. Two of them, Bio1 and Abio1 were able to improve to be moderat resistant (MR) status while Bio2 and Abio2 gave resistant (R) status. The measurement and detection indicated that salicylic acid content tends to increase after inoculation by pathogen P. maydis comparing with control and PR-1 gene was detected respectively.The inheritance study also showed the increased resistance status could be inherited into populations S 1. Under supervision of Dr. Ir. Aziz Purwantoro, M.Sc. and Dr. Ir. Andi Khaeruni R., M.Si. 1 generation seed material. Second experiment is verification of induced resistance status. Investigation was conducted by physiological and molecular approach using salycilic acid content estimation and detection of PR-1 gene using PCR technique. Third is inheritance study in S1 generation from line that possess resistance raising. 1 generation and followed Mendelian inheritance pattern for the ratio 15:1.